Modulating electronic and geometric structure of transition metal compounds for efficient water splitting - Tang, Shasha (Nanyang Technological University, 2020)
Traditional fossil fuels, such as coal, oil, and natural gas, represent more than 85% of the global energy consumption. The excessive use of these traditional fossil fuels has brought environmental problems, such as air pollution and greenhouse effect. Hence, the search of sustainable and renewable energy is of significant importance. In view of the inexhaustible supply of water, hydrogen generation by water electrolysis is a promising strategy to provide sustainable energy source. One of the important factors that constrains the mass production of water electrolysis is lack of efficient and cost-effective catalysts. Thus, developing high efficiency, stable and low cost catalysts is highly desirable for the commercial H2 production from electrochemical/photoelectrochemical water splitting. In order to minimize the cost, non-noble metal based materials are substituting the costly and scarce noble metal materials. In this Thesis, we have investigated different types of transition metal based catalysts for water electrolysis/photoelectrolysis. The synthesis techniques, materials characterizations, and electrochemical/photoelectrochemical performance evaluation of the catalysts are presented in details. Four different catalysts are studied, which are (i) Co3S4 and Ni:Co3S4 nanowires, (ii) oxygen-deficient WO3 microplates, (iii) CoMo2S4 cross-linked porous nanoflakes, and (iv) hierarchical Cu(OH)2@Co(OH)2 nanotrees. We study the above catalysts from different aspects, from materials design, nanostructure engineering, to theoretic calculation. First, we start with transition metal oxide (Co3O4) nanowires and convert to Co3S4 for bifunctional electrocatalytic water splitting. Then we doped the nanowires with Ni elements to obtain Ni:Co3S4. In addition to systematic electrochemical characterization, DFT calculation is applied to determine the Gibbs free energy (ΔG) of the intermediates. It is found that the sulfur element reduces the ΔG of the intermediates and results in lower theoretic overpotential, leading to better HER and OER electrocatalytic performance of the sulfides as compared to the oxides. Additionally, doping Ni also improves the HER performance because of a better intrinsic electrocatalytic activity of Ni as compared to Co. Secondly, the oxygen-deficient WO3 plates are synthesized by a combining technique of hydrothermal treatment and two-step annealing treatment. The commercial tungsten foil acts as the starting material and converts to normal WO3 plates following a hydrothermal and a traditional annealing process. In order to increase the oxygen defects, the above WO3 plates are twice annealed at higher temperature. Oxygen deficiency in WO3 increases the donor density, leading to better charge carrier generation and separation, achieving enhanced the photoelectrochemical performance, such as higher photocurrent density and super stability. Furthermore, the CoMoO6 and CoMo2S4 cross-linked porous nanoflakes are investigated as bifunctional electrocatalysts for overall water electrolysis. The CoMoO6 nanoflakes are synthesized and considered as the starting material. Subsequently, the CoMoO6 sample undergoes an ion exchange reaction in additional hydrothermal process to obtain CoMo2S4. The CoMo2S4 electrode shows a low OER/HER overpotential than that of CoMoO6 electrode. The two-electrode electrolyzer cell (CoMo2S4//CoMo2S4) exhibits efficient overall water electrocatalytic ability and stability. In addition, we present the hierarchical hybrid Cu(OH)2@Co(OH)2 nanotrees as efficient OER electrocatalyst. It is found that forming such core-branch hierarchical nanostructures out of both catalytic active materials is an effective strategy to increase the catalytic active sites, reaction kinetics, and charge transport. Specifically, leaves-like ultrathin Co(OH)2 nanoflakes are grown on the branch-like Cu(OH)2 nanowires via an combined synthesis of an anodization process and a electrodeposition process. This hierarchical Cu(OH)2@Co(OH)2 nanotree electrode shows a low OER overpotential and high stability with negligible degradation, taking advantages from the hierarchical hybrid nanotree structure. Therefore, our material and nanostructure design are effective in improving the catalytic capability of the catalysts. The well-separated hierarchical nanostructure promotes the reaction kinetics and charge transport, facilitates the contact of solid-electrolyte interface and the release of gaseous product. In addition, these catalyst materials are directly grown on conductive substrate support, such as Ni foam, W foil, and Cu foil. This not only enhances the contact surface areas (thus more active sites), but also eliminates the usage of binders. The research in this Thesis provides new possibility of materials design towards low-cost and efficient water electrolysis/photoelectrocatalysis.